Environmental awareness and its relationship with plant literacy and green school management - Dellivio Glementino Dumaili; Tinjung Mary (Universitas Negeri Jakarta, 2026)
Climate change and human activities pose serious threats to the environment, making environmental awareness among younger generations increasingly crucial. Schools play a strategic role in shaping environmental attitudes and behaviors through structured and sustainable education. Strengthening environmental awareness in formal education is essential, as young people will become future decision-makers and agents of change in addressing environmental challenges. Environmental awareness is closely linked to understanding the role of plants and agriculture, which ideally develops through early environmental education. In Indonesia, green school initiatives are implemented through the Adiwiyata program across all school levels. This study examines the environmental awareness of senior high school students and its correlation with their understanding of plants and agriculture as well as their perceptions of green school management. Data were collected from 120 grade 11 students in four high schools (two public and two private) in Salatiga City, Central Java, using questionnaires and supporting documentation. Descriptive statistics and the Spearman Rank correlation test were employed. The findings revealed a strong correlation between students’ environmental awareness and their understanding of the role of plants and agriculture (r = 0.740) and a moderate correlation with green school management (r = 0.488). The study recommends integrating comprehensive and experiential environmental education, particularly focusing on plant and agricultural literacy, to enhance students’ environmental awareness and support sustainable school practices